Safe Use of Glyphosate-containing Products in Aquatic and Upland Natural Areas - Kenneth A. Langeland (EDIS)
Land and water managers who apply herbicides to control invasive plant species and other nuisance vegetation strive to minimize environmental impacts as a matter of policy and daily operations. It is, therefore, not surprising that concern has been expressed and many questions asked relative to recent publications by Relyea (2005a, 2005b, 2005c), which implicate use of glyphosate-containing herbicides in global decline of amphibians. The purpose of this article is to put these recent publications in perspective relative to aquatic and terrestrial natural area weed management and explain why land managers should continue to use glyphosate-containing products to protect managed habitats from weeds without concern for unreasonable adverse environmental impacts. This document is SS-AGR-104, one of a series of the Agronomy Department, Center for Aquatic and Invasive Plants, UF/IFAS Extension. Original publication date February 2006.